Prevalensi Escherichia coli Pada Daging Sapi Di Rumah Potong Hewan Oeba Kota Kupang - Sera Marbella Christin Langgar; Maxs U E Sanam; Annytha Ina Rohi Detha (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2021)
Meat is one of the livestock products that cannot be separated from the needs of human life. The biggest possibility of bacterial contamination can occur in slaughterhouse (RPH). One of the bacteria that can contaminate meat is Escherichia coli. Escherichia coli (E. coli) is a bacterium that normally lives in the digestive tract of animals and humans. In general, E. coli is considered a normal flora in the digestive tract of animals (cows) that can contaminate meat and the environment around the slaughterhouse during the slaughter process. Beef which was contaminated initially accompanied by improper cooking process is a source of infection from several cases of food poisoning, including those caused by STEC. So that it is necessary to increase food safety for foods that come from animals such as beef or the processed of products to be able to guarantee the quality of food that will be consumed by the community and can prevent Foodborn disease. The sampling method was carried out using a purposive sampling method. Isolation and identification of bacteria was carried out on Eosin Methylene Blue Agar (EMBA) media, and then continued with other tests to confirm the positive Escherichia coli bacteria. On Eosin Methylene Blue Agar (EMBA) media, positive colonies of Escherichia coli are metallic green with black spots in the middle. Eosyn Methylene Blue Agar is a differential medium used to distinguish E. coli from other Enterobactericeae. The sample used was beef taken in Oeba RPH Kupang City when the slaughter was in progress. Samples taken were 41 beef samples in Oeba RPH. The results showed that from 41 beef samples, 4 positive samples of Escherichia coli (9,75%).